Education and continuing professional development for Indonesian academic librarians: a survey - Maesaroh, Imas; Genoni, Paul (Emerald Group Publishing Limited, 2009)
This paper reports base-line data on the current levels of education, skills, and knowledge of Indonesian academic librarians, and provides an insight into their continuing professional development. The paper reports: the current level of qualifications of librarians working in Indonesian academic libraries; the current level and type of continuing professional development and work place training in Indonesian academic libraries.The paper includes the results of a questionnaire delivered to all librarians working in Indonesian public universities. The survey instrument was based on that used in the NEXUS survey distributed to Australian ILS professionals in 2006. The paper includes a comparison of survey results on key indicators for Indonesian and Australian library and information staff.